2010
DOI: 10.1039/c002778b
|View full text |Cite
|
Sign up to set email alerts
|

Sm(ii) reduction chemistry of heteroalkynes: stable adducts, reductive coupling, reductive C–C/C–N bond cleavage and trapping of the tert-butyl fragment with bulky nitriles, phosphaalkynes and isonitriles

Abstract: Reactions of a dimetallated N,N'-dimethyl substituted porphyrinogen Sm(II) complex with a series of t-butyl substituted heteroalkynes affords a diverse range of reactivity. The phosphaalkyne t-BuC[triple bond]P gives a dinuclear Sm(III) P-P reductively coupled complex of (t-BuC=PP=C-t-Bu)(2-) featuring a new mu-eta(2)(1,2-C,P) binding mode. In contrast, the nitrile aza analogue t-BuC[triple bond]N forms Sm(II) adducts that undergo reductive C-C bond cleavage at elevated temperatures to afford a trimeric Sm(III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…The reduction of two equivalents of tBuN CD with 1 led to a very different result, namely reductive C À N bond cleavage and the moderate yield formation of the trimeric mag- www.chemeurj.org nesium cyanide complex, 5. It could not be determined what the fate of the cleaved tert-butyl group was in this reaction, but similar reductive N À C cleavages of tBuN C: initiated by Sm II complexes are thought to occur through one-electron processes, yielding the tert-butyl radical and trimeric samarium cyanide complexes, for example, [{L n Sm(CN)} 3 ] (L n = Cp* 2 A C H T U N G T R E N N U N G (tBuNC) [13] or the dianionic porphyrinogen ligand, [14] ). The formation of cyanides through the reduction of isonitriles has been previously achieved using a variety of other reagents, [13] though these reactions generally require harsh conditions to proceed.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction of two equivalents of tBuN CD with 1 led to a very different result, namely reductive C À N bond cleavage and the moderate yield formation of the trimeric mag- www.chemeurj.org nesium cyanide complex, 5. It could not be determined what the fate of the cleaved tert-butyl group was in this reaction, but similar reductive N À C cleavages of tBuN C: initiated by Sm II complexes are thought to occur through one-electron processes, yielding the tert-butyl radical and trimeric samarium cyanide complexes, for example, [{L n Sm(CN)} 3 ] (L n = Cp* 2 A C H T U N G T R E N N U N G (tBuNC) [13] or the dianionic porphyrinogen ligand, [14] ). The formation of cyanides through the reduction of isonitriles has been previously achieved using a variety of other reagents, [13] though these reactions generally require harsh conditions to proceed.…”
Section: Resultsmentioning
confidence: 99%
“…[7] To probe the effect of the unique electronic structure of 1 in single-and multi-electron transformations,weturned our attention to organic isocyanides.Ithas been shown that highly reducing metals (e.g.,S m II and alkali metals) promote CÀN bond cleavage in isocyanides,p resumably through oneelectron processes. [8][9][10] However, the very negative reduction potentials of the Th IV/III and Th III /Th II couples [11][12][13] often prohibit this type of reductive behavior by thorium compounds.T herefore,a ll previous reports discussing the interaction of isocyanides and thorium complexes have described conventional redox-innocent (2 e À donor or insertion) reac-tivity. [14,15] In this work, we utilize the redox non-innocence of 1 to expose an additional facet of thorium-bpy mediated reactivity and report the first examples of reductive R À NC bond cleavage by athorium complex.…”
mentioning
confidence: 99%
“…[15,20] Although this work is the first example of thorium-mediated reductive cleavage of an R À NC bond, the bond activation by 1 advances that seen previously in transition metals and lanthanides. [8,9,21,22] Evans [9] and Schulten [10] introduced Sm II -mediated RÀNC bond cleavage and concluded that single-electron chemistry was probable in the formation of Sm À (CN) derivatives.O ur system goes beyond that, demonstrating that the open-shell singlet (f 1 p* 1 )e lectronic structure of 1 promotes clean RÀNC bond scission chemistry and furnishes av ery well-defined product in which both fragments of the cleaved isocyanide are retained.…”
mentioning
confidence: 99%
“…The solid‐state structure of this complex, as determined by single crystal X‐ray diffraction study, features Sm—C/P short contacts in a μ‐ŋ 2 (1,3‐C, P) fashion and trans ‐geometry (for C=P bonds) of the dianionic bridging ligand. Conversely, when a substituted porphyrinogen was used instead of Cp* as the supporting ligand, a drastically different structural outcome was achieved: the dimerized ( t ‐BuC=P–P=C–t‐Bu) 2– bridging ligand was coordinated in a μ‐ŋ 2 (1,2‐C, P) fashion and in a cis ‐geometry (for C=P bonds) to the Sm(III) cations (Figure B) . This divergent reaction outcome is postulated to be in response to the relief of steric interactions from the porphyrinogen ligand, which has larger steric factors compared to Cp*.…”
Section: Molecular Polyphosphides Of the Rare Earth Elementsmentioning
confidence: 99%
“…Although rare earth polyphosphide/polyarsenide complexes were usually obtained using reductive methods by reacting t ‐BuC≡P or P 4 /As 4 or Cp*Fe(ŋ 5 ‐P 5 )/Cp*Fe(ŋ 5 ‐As 5 ) with divalent rare earth precursors, analogous precursors with heavier pentel elements, namely antimony and bismuth, have been found unreactive under the same reaction conditions. Hence, a number of alternative synthetic methods have been developed toward molecular polystibides/polybismuthides of the rare earth elements.…”
Section: Molecular Polystibides Of the Rare Earth Elementsmentioning
confidence: 99%